Swedish food habits for higher nutritional value and lower climate impact - Johansson, Rebecca; Torstensson, Linn (2021)
In order to tackle climate change and the increased prevalence of non-communicable diseases, a transformation of human diets is urgently needed. The food retailers can play an important role if integrating sustainability related aspects in their corporate portfolio decisions in order to influence the consumer to make more sustainable food choices. This master thesis focuses on dietary habits in the light of portfolio management with guidance from a decision-making tool (Cynefin). If focus on principles to identify food alternatives with lower climate impact and higher nutritional value of dishes that are frequently prepared in a home setting. Their understandings are integrated in portfolio management strategies for sustainable development. It was conducted as a commission from Axfood’s private label brand Garant, which also serves as the case study. The empirical data consists of sales statistics, nutritional guidelines, nutritional content and calculated carbon dioxide equivalents. The results show that commonly consumed dishes exceed goals for climate boundaries and they are nutritionally inadequate. In order to reach targets related to nutritional guidelines and climate impact goals, the content of animal-based products needs to be reduced. Furthermore, vegetables and whole grains need to be increased. The findings of the study provide opportunities to integrate climate and health aspects further in the portfolio management of Garant. Changing dietary habits and integrating sustainability in portfolio management is not a clear and simple road. Rather, it needs to be shaped in accordance to the context of the specific corporation. The results show that integration of sustainability alters the retailer owned brand portfolio management decisions.